Advancements in Plant Protection Technologies and Mechanization in the Russian Federation - A. K. Lysov; T. V. Kornilov (Сельскохозяйственные машины и технологии)
The paper highlights the achievements of domestic scientists, engineers and designers in pesticide application in agriculture. (Research purpose) The study provides a retrospective analysis of the evolution of plant protection technologies and mechanization tools in the Russian Federation. (Materials and methods) The research draws on a variety of sources, including publications in scientific journals, monographs, conference proceedings, archival photographs, and exhibits from the scientific and methodological office (museum) of the All-Russian Research Institute for Plant Protection. (Results and discussion) The paper details the development of domestic horse-drawn, mounted tractor, automobile field and portal garden sprayers in 1931-1941. In the 1960s, research focused on determining the optimal droplet size and phytocidal action radius for low-volume spraying of plant protection products. Aerosol technologies were developed. The paper highlights the contribution of Dr.Sc. V.F. Dunsky in establishing the theoretical foundations of fine-droplet and low-volume spraying physics and technology. It also emphasizes the development and enhancement of plant protection technologies by creating a comprehensive system of machines for agricultural mechanization. This progress was achieved under the scientific and methodological guidance of experts from the All-Russian Institute of Agricultural Mechanization. As the consumption rates of the working fluid decreased, rotary (disk) sprayers became essential for both ground and aerial spraying equipment. To enhance environmental safety, more eco-friendly sprayers were developed with systems for small droplet separation or forced sedimentation, and a method for electrically charging droplets was introduced. Modern approaches to the development of new plant protection technologies are based on the principles of precision farming. These approaches include differentiated crop treatment that considers the spatial heterogeneity in the distribution of harmful organisms within field areas. (Conclusions) Plant protection technologies and mechanization tools evolved and improved with the introduction of new chemical agents. Notably, spectrometry is used to create spectral image libraries of cultivated and weedy, healthy and diseased plants, facilitating the automatic decoding of data collected from field through neural networks (artificial intelligence). Additionally, unmanned aerial vehicles are utilized for the application of plant protection products.